Taken - Henderson, Dee (Bethany House, A division of Baker Publishing Group, 2015)
"Years after being abducted as a teenager and being forced to assist a crime family, Shannon contacts private investigator Matthew Dane for help, desperate for resolution to the mysteries and pain of her past and hoping for the freedom to begin a new life"--